Proton Pump Activation in Stimulated Parietal Cells Is Regulated by Gastric Acid Secretory Capacity: A Human Study - Metz, David C. (J Clin Pharmacol, 2002)
Under normal physiological conditions, gastric acid production is controlled by a negative feedback mechanism. Proton pump inhibitors, such as pantoprazole, inhibit gastric acid secretion by irreversibly binding and inactivating luminally active hydrogen potassium ATPase. Recovery of acid production after treatment with a proton pump inhibitor is driven by new pump synthesis, activation of existing cytoplasmic pumps, or reversal of proton pump inhibition. The authors measured the time course of the inhibition and recovery of acid secretion in healthy volunteers following intravenous administration of pantoprazole to determine the rate of proton pump activation under maximally stimulated conditions. Gastric acid production was measured in 27 Helicobacter pylori negative healthy volunteers (mean age = 31 ± 7 years; 17 men, 10 women) who received single doses of intravenous pantoprazole (20, 40, 80, or 120 mg) in the presence of a continuous intravenous infusion of 1 ug/kg/h of pentagastrin. From the time profile of acid secretion, the authors described the rate of change of acid output using an irreversible pharmacodynamic response model represented by the equation [Formula: see text] and correlated the parameter values with demographic factors and gastric acid measurements. Mean stimulated acid output secretion was 21.6 ± 18.4 mEq/h (range: 1.6–90.5) prior to the administration of pantoprazole and remained steady for 25 hours after placebo administration. Intravenous pantoprazole inhibited acid output in a dose-response fashion, with maximal inhibition (99.9%) occurring after an 80 mg dose. Mean proton pump recovery time was 37.1 ± 21.0 hours (range: 6.7–75), and recovery was independent of the dose of pantoprazole. There was no association noted between proton pump recovery time and gender, age, race, body weight, or pantoprazole dose. However, there was an inverse correlation between acid output during baseline stimulation and recovery of acid secretion. Mean proton pump recovery time in stimulated normal human volunteers was 37.1 ± 21.0 hours, with a range of 6.7 to 75 hours. The authors hypothesize that there may be a normal homeostatic mechanism that maintains acid secretory capability within a normal range by altering the rate of proton pump activation dependent on the individual’s parietal cell mass. Abnormalities of this process may be responsible for the development of acid peptic disease in susceptible individuals.